Micropatterned conductive elastomer patch based on poly (glycerol sebacate)-graphene for cardiac tissue repair. (1st July 2022) - Shi, Mengting; Bai, Lang; Xu, Meiguang; Li, Zhenlong; Hu, Tianli; Hu, Juan; Zhang, Zixi; Yin, Zhanhai; Guo, Baolin
Abstract: Preparing a micropatterned elastomer film with characteristics that can simulate the mechanical properties, anisotropy, and electroactivity of natural myocardial tissues is crucial in cardiac tissue engineering after myocardial infarction (MI). Therefore, in this study, we developed several elastomeric films with a surface micropattern based on poly (glycerol sebacate) (PGS) and graphene (Gr). These films have sufficient mechanical strength (0.6 ± 0.1–3.2 ± 0.08 MPa) to withstand heartbeats, and the micropatterned structure also satisfies the natural myocardium anisotropy in the transverse and vertical. Moreover, Gr makes these films conductive (up to 5.80 × 10 −7 S m −1 ), which is necessary for the conduction of electrical signals between cardiomyocytes and the cardiac tissue. Furthermore, they have good cytocompatibility and can promote cell proliferation in H9c2 rat cardiomyocyte cell lines. In vivo test results indicate that these films have good biocompatibility. Notably, a film with 1 wt% Gr content (PGS–Gr1) significantly affects the recovery of myocardial function in rats after MI. This film effectively decreased the infarct size and degree of myocardial fibrosis and reduced collagen deposition. Echocardiographic evaluation showed that after treatment with this film, the left ventricular internal dimension (LVID) in systole and LVID in diastole of rats exhibited a significant downward trend, whereas the fractional shortening and ejection fraction were significantly increased compared with the control group. These data indicate that this electroactive micropatterned anisotropic elastomer film can be applied in cardiac tissue engineering.